We saw in Spain (pamphlet) - Dugdale, John ; Wilkinson, Ellen Cicely, 1891-1947 ; Noel-Baker, Philip Noel-Baker, Baron ; Malindine, E. G.; Attlee, Clement, 1883-1967
1937 The Children are Spain's Future By ELLEN WILKINSON, M.P. FIFTEEN HUNDRED children, each clutching a mug, stood in a queue. Two helpers, an Englishman and a Spanish woman, were trying to explain to mothers with babies in their arms why no more cards could be handed out. Each child had its cup of milk, dried powder and water, and a biscuit. This week the funds sent devotedly by the Society of Friends were low, and only half the quantity could be given. For many of these children this would be their only meal that day. Towards the end of the queue there was a strange silence. The big dark eyes of the children were fixed with a terrible anxiety on the arms of the helpers as they went deeper and deeper to get at the dwindling supply. I shared their anxiety. I felt I just could not bear it. if those sixes and sevenses had to be told "No more to-day." And these were only fifteen hundred children in a city of a million souls. In the main street outside "Asistencia Social," the great Government welfare organisation, some big lorries were parked. They contained tins of food sent by the women's committee of the French Popular Front. A thin woman with a baby in her arms and another at her skirt, stopped as she passed the lorry and stroked it, as though somehow it could understand her thanks. "Will she have a ticket ?" I asked the efficient young Catalan woman who was my guide. "That is all going out to the refugees in the villages. We have a million to feed," she replied. A school in Madrid - a fine building, one of the fifty built in the short reign of the Republic - big windows, lots of light and air, and the children sitting happily round little tables. All children of the working class, keen as needles, but so thin. Every day they had to come to school through falling shells or casual bullets. The school was only 2½ miles from the actual trenches. Bombs had fallen on schools just like this, wrecking them completely, blowing teachers and children to bits. That, is how the Fascists bring civilisation to a country. "How can you stand it ?" I asked a young teacher. "It's all right if we can keep the children fed. That keeps up their nerves and it is wonderful then what they can resist." "These children are Spain's future — if we can only get them through this time," said the courteous, elderly Head Teacher to Mr. Attlee. Our leader smiled, but his eyes were wet, as we passed through the school. "We'll send you milk, we promise we will," we said as we bade good bye to these teacher-heroines. "But hasn't the Republic got the money to buy food?" We talked to the Premier, Dr. Negrin - the rock of his country's confidence in this crisis. Dr. Negrin is a specialist in physiology. He knows better than anyone what his children need. He knows, too, that these children have to be defended. And the Non-Intervention Committee, which stops no Italian and German arms going to the Fascists, denies him the right to buy legally the means to defend these children. It denies even the anti-aircraft guns to keep off the Fascist bombing planes. To get these - whether by making them in improvised factories in Spain, as they are doing, or from abroad - costs a lot more money than would be needed if ordinary orders could be placed. There is less money for food because of the Non-Intervention Committee. And Franco has the richest agricultural districts and no refugees. The Spanish Republic will win through. How soon depends on us. The soldiers of the Republic are fighting the battle of democracy - our battle. It is our task to see that their children are fed. Mr. Attlee addresses N.C.O.s in their training barracks. Men of this splendid new army are saving Spain. 292/946/18a/69(iii)